Genesa Batugamping Merah Muda Di Daerah Klepu, Kecamatan Kokap, Kabupaten Kulon Progo, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Wanita UGM, 2005)
ABSTRAK The existence of pink and white limestones which are scattered sporadically at Klepu area of Kokap sub-district in Kulon Progo Regency, Special Teritory of Yogyakarta (DIY) is geologically interesting to be explained with respect to their genetic, due to invariably colors white and grayish white. The limestone is one of the other members of Jonggrangan Formation. To explain genetically why the limestone is pink, it is necessary to analyse ,the petrographical, chemical, and normative mineralogical compositions. Stratigraphical information of the area is helpful in this study. Based on this study it is concluded that the existence of titanoferous magnetite with its FeO.Fe203.Ti02 chemical formula and red in color has caused the limestone to acquire the pink color. It has been figured out that the mineral was derived from "Old Andesite Formation" which bears FeO, Fe203, and TiO2 chemical composition. The stratigraphical information which support of the interpretation is the "Old Andesite Formation" has unconformity relation with and older than pink limestone, so when the limestone began to be deposited mechanically, titanoferous magnetite which was from the "Old Andesite Formation" entered into the limestone depositional environment. This process influenced limestone composition and resulted a part of the limestone has pink color syngenetically.